2013
DOI: 10.1038/ncomms3383
|View full text |Cite|
|
Sign up to set email alerts
|

A nanostructured cathode architecture for low charge overpotential in lithium-oxygen batteries

Abstract: The lithium-oxygen battery, of much interest because of its very high-energy density, presents many challenges, one of which is a high-charge overpotential that results in large inefficiencies. Here we report a cathode architecture based on nanoscale components that results in a dramatic reduction in charge overpotential to B0.2 V. The cathode utilizes atomic layer deposition of palladium nanoparticles on a carbon surface with an alumina coating for passivation of carbon defect sites. The low charge potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
362
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(380 citation statements)
references
References 43 publications
12
362
4
2
Order By: Relevance
“…c,d) Reproduced with permission 70. e,f) Reproduced with permission 78. Copyright 2013, Nature Publishing Group.…”
Section: Utilizing Ald For Advanced Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…c,d) Reproduced with permission 70. e,f) Reproduced with permission 78. Copyright 2013, Nature Publishing Group.…”
Section: Utilizing Ald For Advanced Electrode Materialsmentioning
confidence: 99%
“…As an unique surface modification process for electrodes of LIBs, ALD surface coating has been conducted with cathode materials of Li–O 2 battery 77. Utilizing ALD Al 2 O 3 and Pd, Lu et al developed a novel cathode material of palladium nanoparticles and thin alumina layer coated on carbon 78. As shown in Figure 5e–f, the ALD alumina layer effectively protects the carbon surface and prevents the decomposition of electrolytes, while the nanosized Pd electrocatalyst promotes the formation of nanocrystalline discharge product of Li 2 O 2 , which is beneficial for charge transport.…”
Section: Utilizing Ald For Advanced Electrode Materialsmentioning
confidence: 99%
“…Peng et al found that Li–O 2 battery can retain 95% of its capacity after 100 cycles with a low‐charge overpotential by using a nanoporous gold cathode 28. Recent reports have shown that Li–O 2 batteries with noble metal catalysts, such as Pd,29, 30, 31 Ru,32, 33, 34, 35 and Pt,36, 37, 38, 39 exhibited low overpotentials and long‐term cycling stability. To prepare noble‐metal‐based catalysts, a carbon material is usually needed to support the noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, carbon materials suffer from decomposition in the presence of Li 2 O 2 or LiO 2 ,40, 41, 42 especially those with defects 43. In addition, carbon, particularly that contains defects, also catalyzes the electrolyte decomposition during cycling 30, 41. Furthermore, polymer binders are chemically/electrochemically unstable in contact with Li 2 O 2 or LiO 2 44, 45, 46…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation